PCR Primers That Amplify Fungal rRNA Genes from Environmental Samples - Borneman, James (American Society for Microbiology, 2000)
Two PCR primer pairs were designed to amplify rRNA genes (rDNA) from all four major phyla of fungi: Ascomycota, Basidiomycota, Chytridomycota, and Zygomycota. PCRs performed with these primers showed that both pairs amplify DNA from organisms representing the major taxonomic groups of fungi but not from nonfungal sources. To test the ability of the primers to amplify fungal rDNA from environment samples, clone libraries from two avocado grove soils were constructed and analyzed. These soils possess different abilities to inhibit avocado root rot caused by Phythophthora cinnamomi. Analysis of the two rDNA clone libraries revealed differences in the two fungal communities. It also revealed a markedly different depiction of the soil fungal community than that generated by a culture-based analysis, confirming the value of rDNA-based approaches for identifying organisms that may not readily grow on agar media. Additional evidence of the usefulness of the primers was obtained by identifying fungi associated with avocado leaves. In both the soil and leaf analyses, no nonfungal rDNA sequences were identified, illustrating the selectivity of these PCR primers. This work demonstrates the ability of two newly developed PCR primer sets to amplify fungal rDNA from soil and plant tissue, thereby providing unique tools to examine this vast and mostly undescribed community of organisms.